(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: The use of perfluorocarbon liquids (PFCL) and heavy silicone oil (HSO) for post-vitrectomy tamponade would potentially widen the range of indications for and improve outcomes of vitreoretinal surgery. The academic literature is, however, equivocal as to the effect of these substances on the structure and functional state of the retina. Purpose: To ivestigate experimentally the effect of shor-term (14-day) tamponade with PFCL versus HSO on the structure and bioelectric functional activity of the rabbit retina over time. Materials and Methods: A total of 6 Chinchilla rabbits (12 eyes) were used in the study. All animals were subjected to ERG analysis before posterior subtotal pars plana vitrectomy. The tamponade with PFCL and with HSO was performed in the right eye and left eye, respectively, and was removed after 14 days. Retinal structures were examined with light and electron miscroscopy and the second ERG was performed at day 7, day 14 or day 30 after removal of the tamponade. Results: The analysis based on light and electron miscroscopy revealed similar effects of the two substances on the structures of the rabbit retina. Major changes were: (a) hydropic changes in the smooth endoplasmic reticulum of retinal pigment epithelium (RPE) cells, RPE mitochondria, photoreceptor inner segments, and ganglion and M?ller cells, and (b) compensation-and-restoration processes within these cells, which enable normalization of the structures. ERG recordings revealed no significant difference between the effect of PFCL and HSO on the functional activity of the rabbit retina: the amplitude of the response of the inner peripheral retina and that of the inner central retina were increased by 30.1% (supernormal ERG) and 44%, respectively, versus 43% and 64.7%, respectively. Conclusions: Short-term (14-day) tamponades with PFCL and heavy silicone oil have similar effects on on the structure and functional activity of the rabbit retina, with the changes which are reversible and non-degenerative in nature. Restoration of bioelectric activity of the retina to baseline levels after removal of 14-day PFCL and heavy silicone oil tamponades requires a longer period than 30 days.